New national fiscal policy for accelerating regional development of infrastructure in Indonesia - Runjung, R. Muhammad Rouffie Putera Kesuma (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
Over the past few years, regional financing in Indonesia, as regulated by law, has continued to develop. In the beginning, the regional financing schemes in Indonesia and the term used was restricted to the term regional loan, until in 2022, the Government of Indonesia formally issued Law Number 1 of 2022, which as one of the most important issues discussed the expansion of regional debt financing schemes in Indonesia into 3 (three), namely regional loans, regional bonds, and regional sukuk. This research aims to provide a descriptive explanation of the regulation of financing schemes in Indonesia through Law Number 1 of 2022 On Financial Relations between the Central Government and the Regions and Government Regulation Number 1 of 2024 On Harmonization of National Fiscal Policy. This research is based on a literature review by linking the latest regulations related to regional financing schemes in Indonesia with case studies and descriptive explanations related to regional financing schemes consisting of regional loans, regional bonds, and regional sukuk. This study aims to explain the new regional financing system provided by Government Regulations Number 1 of 2024 so that it can be used and implemented by the regional government in financing the development.